Peranan Guru PAI dalam Meningkatkan Prestasi Belajar Peserta Didik pada Era 5.0 di SMA Negeri 2 Jombang - Hanifa, Fithri Lathifatul; Sirojudin, Didin (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The role of an Islamic religious teacher can provide an understanding of religion, which is important for students to know Islamic religious knowledge, and teachers also play an important role in improving students' learning achievements, which is carried out formally and informally by the school. This research aims to determine the role of PAI teachers in improving the academic and non-academic results of students in the 5.0 era at SMA Negeri 2 Jombang. The method used in this research is a descriptive qualitative method. Research data was obtained through in-depth interviews, observation and documentation. The research results show that the role of PAI teachers in improving student learning outcomes in the 5.0 era at SMA Negeri 2 Jombang is as a facilitator of learning and success outside of school, motivator, role model, class management, and evaluator. The strategies used by PAI teachers to improve student learning achievement in the 5.0 era at SMA Negeri 2 Jombang include using digital-based learning models, such as the use of interactive multimedia, learning videos, and e-learning platforms. And also use collaborative learning, such as group discussions and project-based learning. Furthermore, there is also learning that encourages creativity and innovation, such as design thinking and problem-based learning. And with technology in the learning process, such as the use of laptops, projectors and digital learning applications. As well as utilizing social media and online platforms to deliver material and interact with other students outside of class.